Pengaruh Al-Jahiz dan Al-Bayan Wa Al-Tabyin terhadap penulisan kesusasteraan Arab - Zamri Arifin (Penerbit Universiti Kebangsaan Malaysia, 1999)
Al-Jahiz is one of the famous writers of Arabic literatures during the Abbasid period. He wrote many books such as al-Bayan wa al-tabyin, al-Hayawan, al-Bukhala etc.. This article attempts to discuss al-Jahiz’s influence in Arabic literary writing mainly through his work al-Bayan wa al-tabyin. Some writers during and after his period are chosen in order to explore the influence of al-Jahiz in their writings